The Water Deficit Solution in Central Asia: Rrainwater Using - Niyazovich, Prof. Gadaev Abror; Khairullaevich, Yasakov Zikrilla; Anvar, Achilov (European Journal of Life Safety and Stability (2660-9630), 2022)
Central Asian countries have the limited water resources and water demand is rising. Water using and water management shows environmental protection and water saving situation in the regions. This article devoted to the possibilities of using the rain water as an alternative water resource and analyses of the combined technology of the rain water using in the agriculture irrigation system.